STRATEGI PROMOSI ONLINE SHOP MELALUI SOSIAL MEDIA DALAM MEMBANGUN BRAND ENGAGEMENT (Studi Kasus: Promosi Brand Sally Heart Melalui Akun Instagram @ukhtisally) - Fani Puspitasari; Henni Gusfa (Universitas Mercu Buana, 2017)
This qualitative research tried to describe the use strategy promotion in social media instagram, currently used by many companies, organizations, and individuals to create an online shop. They use social media to communicate in promoting the products and the interaction between the company and its customers. Consumers in social media are more interactive, they might be persuaded to do something and be able to receive information from anyone. Companies that use social media need to collaborate with customers to promote their products so that it can make an entanglement between the two. Through the media and content co-creation is an innovation in creating products and experiences of collaboration between consumers and companies that are connected (Beyond Promotion) to build brand engagement. Based on this research, shop online promotional strategies used by Hijab Sally Heart using images and video content on the theme of Muslim and concepts of friendship to create communication with customers through social media Instagram as the media used. The implementation of the content is created, generating a spiritual emotional involvement between the online shop and the consumer.Keywords Marketing Communications, Promotion Strategy, Internet Marketing, Social Media Instagram, Brand Engagement